HAKIKAT DAN FUNGSI SASTRA LISAN DALAM MEMULIAKAN PENDIDIKAN BUDI PEKERTI - Anak Agung Gde Putera Semadi (Widyasrama, 2022)
Balinese Oral literature holds a myriad values ​​of local wisdom which are very useful for glorifying education of character. The noble cultural values ​​implied are full of religious-magical meaning that breathes Hinduism Dresta Bali. Therefore, Balinese oral literature is closely related to traditions and customs that have been passed from generation to generation and from time to time. This assumption underlies the importance of this research to be conducted and the results being published. The object of this research study is the text and its context in society. The descriptive data resulted can be observed and described clearly without using statistical procedures or other quantification ways. The classification of all field data and the results of the literature study are reviewed by using functional theory. Therefore, the application of descriptive analysis method is impossible to be avoided. The sources of data are also strengthened by research instruments in the form of observation guidelines, in-depth interview guidelines, recordings, and document studies. The results of this study shows that Balinese oral literature or folklore has a very strong closeness to the soul of its supporting community. The meaning of the emitted purpose of life is full of Balinese religious activities functions from past to present. Thus, the existence of Balinese oral literature remains important as a fundamental consideration in glorifying the education of character.